Critical parameter determination of sonic flow controller diamond microtubes and micronozzles - Mammana, S. S.; Degasperi, F. T. [UNESP]; Salvadori, M. C.; Sparapani, D. C. [UNESP]; Laino, M. F. [UNESP]; Rangel, R. C. [UNESP]; Teixeira, F. S.; Cattani, M. (American Vacuum Society, 2007)
In this article, the authors measure throughput of sonic diamond microtubes and micronozzles that can work as passive gas flow controllers and flow meters under choking conditions. The behavior of the outlet pressure through the microdevices using an experimental setup with constant volume and constant temperature was determined in order to obtain the critical throughput, the critical mass flow rate, and the discharge coefficients of the diamond sonic microdevices. © 2007 American Vacuum Society.
Keywords: Diamonds; Flow rate; Flowmeters; Throughput; Discharge coefficients; Microdevices; Micronozzles; Microtubes; Sonic flow; Flow control